Effects of Seedling and Plant Spacing on the System of Rice Intensification (SRI) for Spring Rice (Oryza sativa L. Chaite 2) - Dhurba Banjade; Dipak Khanal; Aman Shrestha; Karuna Shrestha (AgroEnvironmental Sustainability, 2023)
System of Rice Intensification (SRI technology) increases rice yields while requiring less water and other inputs. It involves the use of specific management strategies that, when used together, provide rice plants with better-growing conditions than those grown using traditional methods, especially in the root zone. An SRI experiment was conducted from February 27, 2022, to July 11, 2022, in rice farmers' fields in Buddhabhumi Municipality, Nepal, using different spacing and seedlings. Spring rice was grown using the SRI with a variety of seeding and plant spacing. The experiment consisted of three plant spacings: 20 × 20, 30 × 30, and 40 × 40 cm, and two seeding groups: regular seeding and pregerminated seedlings. Characteristics were counted, including the number of tillers per mound, leaves, plant height, tillers per square meter, grain yield, and 1000 kernel weight. The result shows that the 20 cm × 20 cm spacing increased tillers per square meter. The spacing also resulted in much higher grain production of 4.29337 Mt/ha. The 30 × 30 cm plot had the tallest plants at 78.10 cm, much higher than the other plots. Similar crops produced significantly more tillers per mound (22.5) when planted at 40 × 40 cm spacing. Since the crops were planted at 40 × 40 cm, the spacing produced significantly more tillers per mound (22.57) and leaves per mound (73.54). Spacing did not affect test weight, nor did the type of seedlings used.